Immune approaches for the prevention of breast milk transmission of HIV-1. - Lohman-Payne, B; Slyker, J; Rowland-Jones, S (2012)
Mother-to-child transmission (MTCT) of HIV-1 infection remains a significant cause of new HIV-1 infections, despite the increasing implementation of prevention strategies using antiretroviral therapy (ART) and the resulting decline in infections across the developing world. In 2009, the UNAIDS global report estimated 370,000 children under the age of 15 years were newly infected with HIV-1 (refer UNAIDS Report on the global AIDS epidemic, 2010 http://www.unaids.org/globalreport/Global-report.htm), most of whom acquired the infection from their mothers in low- and middle-income countries. Even with substantial progress, challenges remain for poor countries in providing comprehensive screening programs for pregnant women and implementing the full range of prevention services for those identified as HIV-1-infected. Although antiretroviral regimens and risk reduction counseling have been successfully used for pregnant women and their infants in many parts of the developing world, full implementation of these programs remains a challenge in many countries, especially where antenatal clinical attendance and HIV-1 screening is not yet widespread. In addition, potential toxicities of and development of drug resistance to ART in both mother and child are concerns. Therefore, the development of a safe effective immunoprophylaxis regimen begun at birth and continuing during breastfeeding, perhaps alongside neonatal chemoprophylaxis, remains an area of active research interest. An ideal pediatric vaccine for prevention of MTCT (PMTCT) would combine the immediacy of passive immunization designed to protect the infant during the first vulnerable weeks of life with the durability of active immunization to protect against the repeated low-dose homologous virus exposure delivered multiple times a day via breastfeeding. © 2012 Springer Science+Business Media New York.